Unraveling productivity-enhancing genes in Chinese hamster ovary cells via CRISPR activation screening using recombinase-mediated cassette exchange system - Baek, Minhye; Kim, Che Lin; Kim, Su Hyun; la Cour Karottki, Karen Julie; Hefzi, Hooman; Grav, Lise Marie; Pedersen, Lasse Ebdrup; Lewis, Nathan E.; Lee, Jae Seong; Lee, Gyun Min (Metabolic Engineering, 2025)
Chinese hamster ovary (CHO) cells, which are widely used for therapeutic protein production, have been genetically manipulated to enhance productivity. Nearly half of the genes in CHO cells are silenced, which are promising targets for CHO cell engineering. To identify novel gene targets among the silenced genes that can enhance productivity, we established a genome-wide clustered regularly interspaced short palindromic repeats activation (CRISPRa) screening platform for bispecific antibody (bsAb)-producing CHO (CHO-bsAb) cells with 110,979 guide RNAs (gRNAs) targeting 13,812 silenced genes using a virus-free recombinase-mediated cassette exchange-based gRNA integration method. Using this platform, we performed a fluorescence-activated cell sorting-based cold-capture assay to isolate cells with high fluorescence intensity, which is indicative of high specific bsAb productivity (qbsAb), and identified 90 significantly enriched genes. To verify the screening results, 14 high-scoring candidate genes were individually activated in CHO-bsAb cells via CRISPRa. Among these, 10 genes demonstrated enhanced fluorescence intensity of CHO-bsAb cells in the cold-capture assay when activated. Furthermore, the overexpression of the identified novel gene target Syce3 in CHO-bsAb cells resulted in a 1.4- to 1.9-fold increase in the maximum bsAb concentration, owing to improved qbsAb and specific growth rate. Thus, this virus-free CRISPRa screening platform is a potent tool for identifying novel engineering targets in CHO cells to improve bsAb production.
Keywords: Bispecific antibody; Chinese hamster ovary; Chinese Hamster ovary cells; CRISPR; Guide RNA; Novel genes; Palindromic; Recombinases; Syce3; Therapeutic; Animals; Antibodies, Bispecific; CHO Cells; Cricetinae; Cricetulus; CRISPR-Cas Systems; Recombinases; Bispecific antibody; Chinese hamster ovary; CRISPR; gRNA; Syce3; Therapeutic